Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.infsof.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of actionable alert identification techniques for automated static code analysis

Abstract: a b s t r a c tContext: Automated static analysis (ASA) identifies potential source code anomalies early in the software development lifecycle that could lead to field failures. Excessive alert generation and a large proportion of unimportant or incorrect alerts (unactionable alerts) may cause developers to reject the use of ASA. Techniques that identify anomalies important enough for developers to fix (actionable alerts) may increase the usefulness of ASA in practice. Objective: The goal of this work is to sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 50 publications
(283 reference statements)
0
81
1
Order By: Relevance
“…In 2011, Sarah Heckmann et al [37] have made an inventory and evaluation of defects detections technique. To do this work, they first collected articles in scientific journals (ACM, IEEE, Springer); They sorted these articles manually according to their importance in relation to the problem.…”
Section: Defect Detection Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, Sarah Heckmann et al [37] have made an inventory and evaluation of defects detections technique. To do this work, they first collected articles in scientific journals (ACM, IEEE, Springer); They sorted these articles manually according to their importance in relation to the problem.…”
Section: Defect Detection Techniquesmentioning
confidence: 99%
“…As we have just seen, for the renaming of entities this will be an adequate behavior. The reasoning behind this decision was that research showed that the majority of programmers did not care about violations [37]. Therefore, a violation may go unnoticed for a long period of time before it simply disappears due to unexpected changes in the source code.…”
Section: Some Terminologiesmentioning
confidence: 99%
“…This fails for situations where a programmer writes code that performs as intended and does not wish to modify. We therefore use the term actionable alert (AA) to define a SA alert that the programmer would act on to resolve and unactionable alert (UA) to define a SA alert that the programmer would not act on to resolve [15].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the prevalence of unactionable alerts in SA warnings, considerable work has attempted to predict whether alerts are actionable or not; Heckman and Williams survey this literature [15]. Of particular importance in this research are the set of characteristics used to predict what SA alerts are actionable or unactionable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation